(untitled) (Bangladesh Journal of Bioethics, 2012)
Dissection of dead body is a time honoured part of medical education. Undergraduate and postgraduate students do dissection as a part of the learning human anatomy. According to the state regulations, most of the cadavers are obtained from the forensic mortuary declared as unclaimed body. Some are collected through body donation as well. However, use of human tissue for research and the use of human cadavers for teaching and training purposes are surrounded by ethical uncertainties. Moreover, the main ethical concern of cadaver dissection lies in respect to human life. This writing has been aimed to put a nominal guideline how to act in an ethical way in cadaver dissection by the medical students in medical colleges and pave the way for better understanding how to respond in an ethical manner in medical professional life. Some rules and regulations have been recommended for maintaining the highest standard of a dissection hall as well as the dignity of the cadavers. DOI: http://dx.doi.org/10.3329/bioethics.v2i3.10258 Bangladesh Journal of Bioethics 2011;2(3):10-15